Thermal Effect in Opal Below Room Temperature - Buerger, Martin J. (1972)
Opal, once believed to be amorphous silica, was shown by Levin and Ott (1932, J. Amer. Chem. Soc. 54, 828-829) to give an x-ray powder pattern of the high-temperature form of cristobalite. The early explanation of this anomalous existence of a phase below its high-low transition temperature is now known to be untenable. One of us suggested that the tiny sizes of the component cristobalite crystals might explain the anomaly; if so, the transition might be expected below ambient temperatures. The record of a du Pont 900 Thermoanalyzer indeed revealed heat effects in opal below ambient temperatures, with an exotherm having a maximum at about -40° on cooling and an endotherm that began about -50° on heating. This was not a latent-heat effect due to the high-low transition of cristobalite, however, for the low-cristobalite pattern persisted to below -50°. Opal normally contains 4-9% water, which is tenaciously held; water loss is nearly linear with temperatures up to about 422°, when water loss is abruptly complete. Water-free opal does not display the thermal effect, but the same opal rehydrated does display it. Water is housed in minute voids, judged to be a few hundred Ångströms across, between minute particles of cristobalite. This water behaves differently from water in bulk, for its begins to melt at about -50°.